Understanding student's intention to pursue a career: Implications for the accounting profession - Sondakh, Jullie Jeanette; Tulung, Joy Elly (Journal of Education and e-Learning Research, 2024)
This study aims to predict accounting students' inclination toward a career in accounting in Indonesia by integrating the Social Cognitive Career Theory (SCCT) and the Theory of Reasoned Action (TRA). The research relies on primary data obtained through an online, closed-ended questionnaire. We employ Structural Equation Modeling (SEM) for the analysis, utilizing statistical tools like SPSS 24.0 and AMOS 24.0 software. Findings from the survey conducted among final-year accounting students in three Indonesian tertiary institutions reveal that self-efficacy impacts the behavioral intention to pursue an accounting career, mediated by outcome expectations, subjective norms, and attitudes. The study identifies both direct and indirect influences of self-efficacy on the behavioral intention. The study innovatively combines the TRA and SCCT models, utilizing a questionnaire to assess the effects of the Association of Southeast Asian Nations (ASEAN) Economic Community on graduates opting for accounting careers within the TRA and SCCT frameworks. Based on the results, integrated career choices must be considered when choosing a career in accounting or other professions. Intervention in an accounting course will help increase the final-year accounting student’s understanding of the accounting profession, including relevant work experience and professional accounting membership.